WTO Disciplines and Fisheries Subsidies - Should the SCM Agreement" Be Modified? - Delvos, Oliver (Victoria University of Wellington Law Review, 2006)
This article considers the negotiations on a possible modification of the World Trade Organization (WTO) Agreement on Subsidies and Countervailing Measures (SCM Agreement) in relation to fisheries subsidies. The mandate for these negotiations was given by the Doha Ministerial Declaration of 2001. The current WTO regulations are deficient in that many subsidies do not meet certain criteria of the SCM Agreement. This is mainly due to the current definition of a subsidy, the requirements for specificity and the inadequate categorisation of "red box" and "amber box" subsidies. In order to address fisheries subsidies adequately, this article contends that the SCM Agreement must be changed. The United States, the European Community, several developing countries and Japan are actively discussing this issue. After examining the different proposals, the best solution seems to be to find a common categorisation for fisheries subsidies and to identify those which lead to over-capacity and over-fishing. Such subsides should be prohibited and named in an illustrative list. Furthermore, subsidies which are not reported to the WTO should be actionable. Any country which has not fulfilled its notification duties would have the burden of proving that these subsidies are consistent with the SCM Agreement. Under new WTO rules, subsidies which are beneficial for the environment should be permitted, such as subsidies for the retirement of fishing licences, the retraining of fishers and the scrapping of old vessels.